Development of a grid-connected electricity supply system using solar energy - Seen, Jian Yi Roger. (2009)
Fossil fuels have been declining at a rapid rate and the use of fossil fuels has also been the cause for environmental hazards. Thus, there is growing concern globally on the need to look for renewable energy. Solar energy has been identified as one of main sources of renewable energy in the future. The geographical location of Singapore has made her an ideal area to implement solar energy as there would be a great amount of sunlight available throughout the year. As such, the Singapore government has already made their official intentions clear that and identify the photovoltaic industry as an emerging industry. The report provides the details for the development of a grid-connected electricity supply system. In this report, there would be a literature review of Photovoltaic applications and its related theory. There would also be the discussion on the implementation, testing and analysis of the work done. The focus of the report would be on the research and implementation of DC-DC converter, DC-AC inverter and Maximum Power Point Tracking (MPPT) of Photovoltaic (PV) module. Details of some of the testing procedures and results for the design systems implemented would also be included in the report for discussions and verification. Lastly, there would be a conclusion to give an overall summary of the project and recommendation for enhancements to improve the systems designed.